Personal Financial Literacy and Financial Planning in Klang Valley, Malaysia - Hoe, Siew Yee (2008)
The financial planning industry in Malaysia is still very much at its inception stage. Currently, regulators- Bank Negara Malaysia and Securities Commission of Malaysia have started to regulate the industry by imposing requirements for whoever wanted to venture into the financial planning profession. The title of ‘Financial Planner’ is now highly legalized by the authorities. Empirical studies have been done by overseas scholars and found that the lack of personal financial literacy has been the impediments to a proper financial planning in life. Therefore this study was designed to determine the relationship of personal financial literacy and financial planning of selected population in Klang Valley, Malaysia. Data for this study were collected by conducting personal interview and by using questionnaires administered in selected shopping malls in Klang Valley. A total of 160 respondents responded to the survey questions. Frequencies, cross tabulation, and Pearson Chi-square test statistics were used to analyze the data. An alpha 0.05 level of significant was used to test the hypothesis for this study. Some of the major findings derived from this study were (1) respondents with high literacy show positive responses on various aspects in financial planning and vice versa; (2) generally respondents’ understanding on various aspects in financial planning is still not satisfying. Recommendations on raising awareness of financial literacy and financial planning were suggested subsequently.